2018
DOI: 10.21451/1984-3143-ar2018-0087
|View full text |Cite
|
Sign up to set email alerts
|

The effects of biological aging on global DNA methylation, histone modification, and epigenetic modifiers in the mouse germinal vesicle stage oocyte

Abstract: A cultural trend in developed countries is favoring a delay in maternal age at first childbirth. In mammals fertility and chronological age show an inverse correlation. Oocyte quality is a contributing factor to this multifactorial phenomenon that may be influenced by age-related changes in the oocyte epigenome. Based on previous reports, we hypothesized that advanced maternal age would lead to alterations in the oocyte's epigenome. We tested our hypothesis by determining protein levels of various epigenetic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 105 publications
(101 reference statements)
2
16
0
Order By: Relevance
“…In this study, we established that among children diagnosed with MIH, who had older siblings, a higher level of global DNA methylation was observed in comparison with children who were born earlier, an outcome which might be linked with the age of the mother. Marshall et al observed a higher level of global DNA methylation in oocytes of aged female mice in comparison to young females [ 18 ]. On the other hand, Markunas et al identified a distinctive pattern of reduced DNA methylation in the blood of infants, which was correlated with the mother’s age at the time of labor [ 19 ], but they were not able to explain the mechanism through which the mother’s age impacts on the creation of permanent epigenetic alterations in offspring and suggested that these might be caused by inheritance of an altered maternal chromatin state.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we established that among children diagnosed with MIH, who had older siblings, a higher level of global DNA methylation was observed in comparison with children who were born earlier, an outcome which might be linked with the age of the mother. Marshall et al observed a higher level of global DNA methylation in oocytes of aged female mice in comparison to young females [ 18 ]. On the other hand, Markunas et al identified a distinctive pattern of reduced DNA methylation in the blood of infants, which was correlated with the mother’s age at the time of labor [ 19 ], but they were not able to explain the mechanism through which the mother’s age impacts on the creation of permanent epigenetic alterations in offspring and suggested that these might be caused by inheritance of an altered maternal chromatin state.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are matching with the study designed by Marshall and his colleagues where they found an increase in the level of global DNA methylation in aged women compared to young women. 19 It is worth mentioning that DNA methylation plays a critical role in transcriptional suppression and chromatin compaction. Therefore, the increase in the level of global DNA methylation with increased female age is a contributor to the alteration of oocyte transcription which influences the development of the embryo.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] A previous study found an association between the increase in DNA methylation level and advancing age. 19 Due to the lack of available information and variances in the results of studies that evaluate the relationship between the global DNA methylation, ICSI outcomes and maternal age. This study was designed in order to investigate the influence of maternal age on the ICSI outcomes which included the number of collected oocytes, mature oocytes, fertilization rate, number of embryos transferred in women undergoing to first ICSI cycle, evaluate the impact of maternal age on the global DNA methylation and study the association between maternal age and other investigated clinical parameters.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Yu et al conducted mRNA-Seq and genome-wide DNA methylation studies in human ovarian GCs and found that compared with young healthy donors, older women with a natural age-related decline in ovarian function showed lower gene expression (1,809 genes were downregulated) that was correlated with higher gene body methylation and 3′-end GC density ( Yu et al, 2015 ). According to Marshall et al, the expression level of the DNA methyltransferase Dnmt1 in oocytes increased in 69- to 70-week-old mice compared with 10- to 13-week-old mice, and the DNA and histone H3K9me2 methylation levels also increased ( Marshall et al, 2018 ). However, Yue et al found that the DNA methylation level of metaphase II (MII) oocytes in 35- to 40-week-old mice decreased compared with six- to 8 week-old mice, and the expression levels of Dnmt1, Dnmt3a, Dnmt3b, and Dnmt3L decreased ( Yue et al, 2012 ).…”
Section: Epigenetic Mechanisms Regulating the Occurrence And Developm...mentioning
confidence: 99%